Flora of Bandhavagarh - Tiwari, S. D. N. (Indian Forester, 1968)
This paper deals with Flora of Bandhavagarh which has been collected during 3 different periods of a year. The total list of plants found in this locality and included in this paper is 553 belonging to 362 genera and 94 families. Bandhavagarh is entirely a new locality for exploration of flora and it should prove an important landmark to Botanists . In 1963, Sarvashri K.M. Sebastine and N.P. Balkrishnan published a paper on the Flora of North-Eastern Madhya Pradesh in the Indian Forester and enumerated 397 species from 85 families. In this region Bandhavagarh is a well known place with a long historical background and now falling entirely in a forest belt. With the expectations that this area may provide valuable floral collections, Botanical expedi- tions were made in September, December and March from 1965 onwards and 553 species from 362 genera and 94 families were collected or observed and are included in this paper. The species which have been included in the paper by Sarvashri K.M Sebastine and Balkrishnan are marked with asterisk. The number of additional species over those described in the above paper is 390 and the number of additional families is 19. With more excursions and intensive explorations this list may further be enlarged. Even in this list several plants of non-flowering families and other improperly recorded species have been excluded.